2007
DOI: 10.1016/j.virol.2006.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Matrix protein of VSV New Jersey serotype containing methionine to arginine substitutions at positions 48 and 51 allows near-normal host cell gene expression

Abstract: The matrix (M) protein of vesicular stomatitis virus (VSV) plays significant roles in the replication of VSV through its involvement in the assembly of virus particles as well as by facilitating the evasion of innate host cell defense mechanisms. The presence of methionine at position 51 (M51) of the matrix (M) protein of the VSV Indiana serotype (VSV(Ind)) has been proven to be crucial for cell rounding and inhibition of host cell gene expression. The M protein of VSV(Ind) with the substitution of M51 with ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…We have inserted the HIV-1 env gene into two different sites in the VSV NJ genome (between the P and M genes and between the G and L genes) and recovered recombinant VSV-HIV-1 gp160 viruses (NP-gp160-MGL and NPMG-gp160-L, respectively) by using the VSV reverse genetics system (Kim & Kang, 2007). We demonstrated that the VSV NJ vector can tolerate a large foreign gene insertion at a position between either the P and M or G and L genes.…”
mentioning
confidence: 99%
“…We have inserted the HIV-1 env gene into two different sites in the VSV NJ genome (between the P and M genes and between the G and L genes) and recovered recombinant VSV-HIV-1 gp160 viruses (NP-gp160-MGL and NPMG-gp160-L, respectively) by using the VSV reverse genetics system (Kim & Kang, 2007). We demonstrated that the VSV NJ vector can tolerate a large foreign gene insertion at a position between either the P and M or G and L genes.…”
mentioning
confidence: 99%
“…Kim and Kang (2007) found that mutations introduced into the M gene of VSV result in an attenuated virus that exhibits reduced inhibitory effects on host cell gene expression and results in significantly less cytopathic effects within infected cell lines, a finding allowing for the production of avirulent and temperature-sensitive VSV mutants. Most valuable is the existence of VSV in two serotypes; Indiana (VSVInd) and New Jersey (VSVNJ).…”
Section: Background and Rationalementioning
confidence: 99%
“…Cells were recovered by centrifugation at 4500 rpm at 4 °C for 10 minutes. according to the manufacturer's specifications in order to recover the recombinant VSVInd(GML)HIV-1gag-env by the VSV recovery protocol (Kim & Kang, 2007). Confluent BHKT7 cells were transfected with 19.4 μg of the plasmid containing VSVInd(GML)HIV-1gag-env and co-transfected with 10 μg of pKS-HP, 10 μg of pKS-HN, and 5 μg of pKS-HL plasmid DNA.…”
Section: (3) Transformation Of E Coli Dh5αmentioning
confidence: 99%
“…One could imagine a scenario where this offers VSV an advantage of having different populations of M: (1) a population with the N-terminal amino acids important for membrane binding and budding activity that is used for assembly of progeny virions and (2) a population without those amino acids that cannot be sequestered to the cellular membranes as readily and therefore could interact with NPCs and cause other cytopathic effects. Not only has this been shown for VSV Indiana M protein but it has recently been shown that methionines 48 and 51 of the VSV New Jersey M protein have similar requirements for CPE (104).…”
Section: Inhibition Of Host Gene Expression By M Proteinmentioning
confidence: 98%
“…The region on the M protein that is responsible for this interaction has been mapped to amino acids 51-59 with methionine 51 (M51) being the most important for colocalization to NPCs and inhibition of nucleocytoplasmic transport (168). Recently, it was also shown that the VSV New Jersey M48 and M51 residues are important for inhibiting gene expression, suggesting that these may be involved in a similar mechanism for this M protein (104).…”
Section: Inhibition Of Host Gene Expression By M Proteinmentioning
confidence: 99%